Investigation of Intermolecular Interactions of 2-Acetoxybenzoic Acid with Hirshfeld Surfaces - Kebiroğlu, Mehmet Hanifi; Yılmaz, Mücahıt (My University, 2025)
In this study, the crystal structure and intermolecular interactions of acetoxybenzoic acid were analyzed. Through crystal structure analysis, the arrangement of carbon (C), oxygen (O), and hydrogen (H) atoms, along with their chemical bonds, was determined. It was identified that oxygen atoms impart polar character to the molecule and play a significant role in intermolecular interactions, such as hydrogen bonding. Hirshfeld surface analysis, performed using CrystalExplorer software, focused on the interactions of the molecule with solvent molecules. This analysis provided a more comprehensive understanding of molecular interactions and structure. Additionally, properties such as electron density, curvature, and surface shape indices were mapped. The structural and electronic properties of acetoxybenzoic acid were visualized, offering a deeper understanding of its chemical and physical properties. XRD analysis revealed the crystallinity of the molecule and provided detailed insights into the crystal structure through the position of the peaks. This study illuminated the molecular structure and interaction properties of acetoxybenzoic acid, contributing to predictions of reactivity at the molecular level.
Keywords: XRD; Acetoxybenzoic Acid; Crystal Structure Analysis; Hirshfeld Surface Analysis